Pest categorisation of Anthonomus grandis. (11th December 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; Navarro, Maria Navajas; Niere, Björn; et al.
Abstract: The European Commission requested EFSA to conduct a pest categorisation of Anthonomus grandis (Coleoptera: Curculionidae), an oligophagous pest weevil feeding on Malvaceae, including Gossypium spp., Hampea spp., Cienfuegosia spp. and Hibiscus pernambucensis . Marginal reproduction has also been observed on the ornamental Hibiscus syriacus . A. grandis is a taxonomic entity with reliable methods available for identification. It is regulated in the EU by Council Directive 2000/29/EC where it is listed in Annex IIB as a harmful organism whose introduction into EU Protected Zones (PZ) (Greece and the Spanish Communities of Andalusia, Catalonia, Extremadura, Murcia and Valencia) is regulated. A. grandis is native to tropical regions of Mesoamerica and has spread to other cotton‐growing areas in the Americas, from the USA to Argentina, causing significant damage to this crop. An eradication programme is in progress in the USA and has been successful in 16 previously infested states. In the EU, phytosanitary measures are in place in order to limit entry via traded commodities. Cotton seeds and fruit, as well as unginned cotton are currently regulated for the PZ but remain a potential pathway. Furthermore, ornamental Malvaceae (e.g. Hibiscus spp.) originating in infested areas may provide additional pathways. The EFSA Plant Health Panel concludes that A. grandis could establish and spread in the cotton‐growing areas of southern EU. Considering the criteria within the remit of EFSA to assess the status as a potential Union quarantine pest (QP), as a potential protected zone quarantine pest (PZQP), or as a potential regulated non‐quarantine pest (RNQP), A. grandis satisfies with no uncertainties the criteria to be regarded as a Union QP. However, it does not meet the criterion of occurrence in the EU territory (for PZQP) plus that of plants for planting being the principal means of spread (for RNQP).